A Co3O4-CDots-C3N4 three component electrocatalyst design concept for efficient and tunable CO2 reduction to syngas. Issue 1 (December 2017) - Guo, Sijie; Zhao, Siqi; Wu, Xiuqin; Li, Hao; Zhou, Yunjie; Zhu, Cheng; Yang, Nianjun; Jiang, Xin; Gao, Jin; Bai, Liang; Liu, Yang; Lifshitz, Yeshayahu; et al.
Abstract Syngas, a CO and H2 mixture mostly generated from non-renewable fossil fuels, is an essential feedstock for production of liquid fuels. Electrochemical reduction of CO2 and H+ /H2 O is an alternative renewable route to produce syngas. Here we introduce the concept of coupling a hydrogen evolution reaction (HER) catalyst with a CDots/C3 N4 composite (a CO2 reduction catalyst) to achieve a cheap, stable, selective and efficient route for tunable syngas production. Co3 O4, MoS2, Au and Pt serve as the HER component. The Co3 O4 -CDots-C3 N4 electrocatalyst is found to be the most efficient among the combinations studied. The H2 /CO ratio of the produced syngas is tunable from 0.07:1 to 4:1 by controlling the potential. This catalyst is highly stable for syngas generation (over 100 h) with no other products besides CO and H2 . Insight into the mechanisms balancing between CO2 reduction and H2 evolution when applying the HER-CDots-C3 N4 catalyst concept is provided. Simultaneous electrochemical reduction of CO2 and H+ /H2 O is an attractive renewable route to produce syngas mixtures. Here, the authors introduce a ternary Co3 O4 -CDots-C3 N4 electrocatalyst that couples hydrogen evolution and CO2 reduction catalysts and achieves cheap, stable and tunable production of syngas.